2003
DOI: 10.1007/s00422-002-0373-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control of sensory gating in a computer model of the CA3 region of the hippocampus

Abstract: A model of the CA3 region of the hippocampus was used to simulate the P50 auditory-evoked potential response to repeated stimuli in order to study the neuronal circuits involved in a sensoryprocessing deficit associated with schizophrenia. Normal subjects have a reduced P50 auditoryevoked potential amplitude in response to the second of two paired auditory click stimuli spaced 0.5 s apart. However, schizophrenic patients do not gate or reduce their response to the second click. They have equal auditory-evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 101 publications
0
36
0
Order By: Relevance
“…Previous modelling studies have explored the local processing and afferent activity in-3 volvement in sensory gating [9,15,14]. Moxon et al [15,14] have explained the nicotinic cholinergic input role in sensory gating and the dopaminergic modulation of the P50 (N40).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous modelling studies have explored the local processing and afferent activity in-3 volvement in sensory gating [9,15,14]. Moxon et al [15,14] have explained the nicotinic cholinergic input role in sensory gating and the dopaminergic modulation of the P50 (N40).…”
Section: Introductionmentioning
confidence: 99%
“…Moxon et al [15,14] have explained the nicotinic cholinergic input role in sensory gating and the dopaminergic modulation of the P50 (N40). In addition they have suggested that GABA B synapses are involved in suppressing the second (test) tone, by suppressing cortical input and recurrent excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Desensitization of receptors with the 1.0 mol/kg dose of ABT-107 may be one explanation for a lack of in vivo efficacy in the DBA/2 sensory gating model. Activation of ␣7 nAChRs on GABA-containing hippocampal interneurons is thought to be a neuronal substrate for sensory gating (Miller and Freedman, 1995;Moxon et al, 2003), and desensitizing this inhibitory system would result in reduced control over excitatory pyramidal neuron firing. Populations of nAChRs may exist between the activated and desensitized states at the same time (Picciotto et al, 2008), and perhaps a net activation is being produced by ABT-107 at plasma concentrations of ϳ1 to 2 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…One neural circuit that mediates both sensory and sensorimotor gating connects the medial septum (Ma and Leung 2007;Ma et al , 2009Miller and Freedman 1993) to the hippocampus (Bast and Feldon 2003;Miller and Freedman 1995), nucleus accumbens, and then ventral pallidum (Arai et al 2008;de Bruin et al 2001;Kretschmer and Koch 1998;Swerdlow and Geyer 1990). Within this neural circuit, dopamine in the nucleus accumbens (de Bruin et al 2001;Swerdlow and Geyer 1990), glutamate, and GABA in the medial septum Leung 2000, 2007;Ma et al , 2009, hippocampus (Moxon et al 2003;Hershman et al 1995), and ventral pallidum (Arai et al 2008;Swerdlow and Geyer 1990) participate in mediation of the gating phenomena.…”
Section: Introductionmentioning
confidence: 96%